A novel sparse boosting method for crater detection in the high resolution planetary image. Issue 5 (1st September 2015) - Wang, Yan; Yang, Gang; Guo, Lei
Highlights The SparseBoost method integrates an improved sparse kernel density estimator into the Boost algorithm. The RSDE-WL1 estimator is achieved by introducing weighted l1 penalty term. An iterative algorithm is proposed to implement the RSDE-WL1 and the proper choice of parameters is discussed.